Legal Analysis of the Prevention of Marine Microplastics Pollution - Hanxia Ran (Law and Economy, 2022)
The protection of marine environment and the preservation of marine ecology are closely related to everyone. However, due to the increase of human social resource consumption and the relative lack of social awareness of marine ecological environment protection, a large number of industrial products are discharged into the ocean, which poses a serious threat to the marine ecological environment. Plastic products are widely used in society because of their low cost, small volume and light weight. A considerable part of waste plastic products flow into the ocean and gradually decompose into microplastic waste. At first, the pollution problem of microplastic waste did not attract enough attention. However, with the continuous deterioration of the marine environment and the destruction of marine biological habitats, the international community has paid more and more attention to this problem and raised the priority of the prevention of marine microplastic pollution. The most obvious manifestation is that the proportion of the resolutions about the management of marine microplastic pollution is increasing in the resolutions of the United Nations General Assembly. There are more and more researches on the prevention and control of marine microplastic pollution in the academic circles of natural science and social science. This paper analyzes the shackles of marine microplastic pollution prevention and control from the perspective of international law, such as difficulties in international legislation, unclear distribution of jurisdiction and responsibility, obstacles in the transformation of international law and domestic law, and the lack of foundation for international cooperation. Although there are many obstacles to the prevention and control of marine microplastic pollution, countries should still adhere to the concept of “Maritime Community with a Shared Future” in marine governance, cooperate with each other, mainly in prevention and secondly in governance, and jointly maintain the marine ecological environment.